Organizational Intelligence for Change Adaptability : The Knowledge, Learning, and Collaboration Cultures Approach - Kucharska, Wioleta, 1977- (Routledge, Taylor & Francis Group, 2025)
This book offers a pioneering exploration of how the synergy between knowledge, learning, and collaboration (the KLC approach) drives organizational intelligence and adaptability. Grounded in empirical research and case studies, it examines how the impact of the KLC approach varies based on company culture (adhocracy, clan, market, and hierarchy) and management levels (team, division and organization).Readers will discover actionable strategies for fostering collective intelligence and adapting to change, especially in the context of remote work and AI-driven environments. The book highlights the critical role of leaders as architects of company culture and provides practical guidance for aligning culture with business goals. Case studies bring the concepts to life, offering valuable lessons for designing and sustaining a growth-agile mindset.This research-rich volume is an essential resource for researchers, academics, and students in organizational change, knowledge management, and strategy, as well as business leaders seeking to enhance their company's collective intelligence and adaptability.
Keywords: Organizational change -- Technological innovations.; Organizational learning -- Technological innovations.; Artificial intelligence.; elektronické knihy; electronic books